Step-by-step explanation:
y = ax^n + bx^(n-1) ... + z
(0, 1) tells us that the constant term z = 1.
because x = 0 eliminates all other terms. and as the sum is 1, that means z = 1.
for the other pairs I strongly suspect
(-1, 3) : 2×(-1)² + 1 = 2×1 + 1 = 3
(-2, 9) : 2×(-2)² + 1 = 2×4 + 1 = 9
so, the fitting equation is
y = 2x² + 1
The rule for quotients of similar bases with different exponents is:
(a^c)/(a^b)=a^(c-b) in this case:
15^18/(15^3)=15^15
Answer:
x = 11
Step-by-step explanation:
Given :
AB = x + 5
BC = 2(x - 3)
AB = BC
AB = BC
x + 5 = 2(x - 3)
x + 5 = 2x - 6
5 + 6 = 2x - x
11 = x
x = 11
happy to help :)
The fourth one I think hope it helps
Answer:
D
Step-by-step explanation: